2019
DOI: 10.1177/1591019919880426
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular preoperative embolization for temporomandibular joint replacement surgery

Abstract: Background and purpose This retrospective study evaluates the safety and effectiveness of preoperative endovascular embolization in patients who underwent temporomandibular joint (TMJ) replacement surgery. Material and methods We included all patients treated with preoperative embolization of the internal maxillary artery (IMAX) between June 2016 and January 2019. All patients were treated by the same surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Prophylactic embolization to reduce the risk and degree of hemorrhage related to TMJ ankylosis surgical repair has been reported mostly in adults utilizing liquid agents or coil embolization. 1618 TMJ ankylosis may require repeated surgical interventions, so the permanent nature of occluding the IMAX trunk by packed coils can be beneficial, as evidenced in our study where 3 patients (50%) underwent repeat surgical procedures without the need for blood product replacement.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Prophylactic embolization to reduce the risk and degree of hemorrhage related to TMJ ankylosis surgical repair has been reported mostly in adults utilizing liquid agents or coil embolization. 1618 TMJ ankylosis may require repeated surgical interventions, so the permanent nature of occluding the IMAX trunk by packed coils can be beneficial, as evidenced in our study where 3 patients (50%) underwent repeat surgical procedures without the need for blood product replacement.…”
Section: Discussionmentioning
confidence: 71%
“…Having a higher risk of non-target embolization to the orbit or brain by reflux or through collaterals. 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients that undergo TMJR are susceptible to potentially life-threatening vascular injury, most commonly of the IMAX. It is well established that preoperative embolization can reduce the risk of blood loss from inadvertent vascular injury and from surgical approach/dissection [ 11 ]. Cillo et al reported that in addition to IMAX, the MMA also may be injured during TMJR which involves extensive dissection, as in an eTMJR case [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous tissues such as ear cartilage, temporalis muscle flap, dermis, fat, and bone, have been used after gap arthroplasty. [ 18 19 ]…”
Section: Discussionmentioning
confidence: 99%